Dampak Kompetensi dan Disiplin Kerja Terhadap Kinerja Pegawai - Montgomery Warbal; Johny Urbanus Lesnussa (Journal of Business Application, 2023)
This research is a quantitative research type which aims to determine the effect of competence on the performance of Supervisors at the Library and Archives Service of Maluku Province and to determine the effect of work discipline on the performance of Employees at the Library and Archives Service of Maluku Province. The variable used in this study is the dependent variable is employee performance and the independent variable is competence and work discipline. This research is located at the Maluku Province Library and Archives Service with a total of 60 employees as the research population and the sampling technique used is the total number of Census points (number), so the sample in this study is 60 samples. The data collection technique used was a questionnaire. Meanwhile, data analysis techniques used multiple linear regression analysis and hypothesis testing using SPSS 16 For Windows. The results showed that: a) Competence (X1) has a positive and significant effect on the performance of Supervisors at the Maluku Province Library and Archives Service with a sig value of 0.005 <0.05. b) Work discipline (X2) has a positive and significant effect on employee performance at the Maluku Province Library and Archives Service with a sig value of 0.002 <0.05.